Strategies for Increasing the Income of Wild Honey Collectors (Apis Dorsata) in Kobisonta Village, East Seram Seti District, Central Maluku Regency - Pratiwi, Nur Muslimah; Lasaiba, Mohammad Amin; Salakory, Melianus (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
This study examines the processing of wild honey (Apis dorsata) as a means to increase the income of the community, particularly the honey processors in Kobisonta Village, East Seram Seti District, Central Maluku Regency. The research then develops strategies for further development. The method used in this study is a mixed-method approach, combining qualitative and quantitative research. The qualitative research uses descriptive analysis, while the quantitative research employs multiple linear regression analysis to predict the effect of independent variables on the dependent variable and SWOT analysis to develop strategies for increasing the income of honey processors.The results of the study indicate that, partially, the variables of education, business duration, and capital have a significant impact, with a significance value of sig = 0.000 < 0.05. However, the number of dependents has little effect. Simultaneously, all four variables are significant, with a significance value of sig = 0.000 < 0.05. Based on the strategies developed using the SWOT model, several strategies were identified: for the S-O strategy, enhancing the production of higher-quality honey, pioneering new marketing areas, and increasing production volume; for the W-O strategy, providing guidance and honey processing technology, establishing institutions, securing government support, and promoting appropriate innovations; for the S-T strategy, building consumer confidence and support, forming partnerships, and establishing regulations by the government and other promotional agents; and for the T-W strategy, restoring and reforesting areas and ensuring hygienic product packaging.